1999
DOI: 10.1093/intimm/11.5.627
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 may be a limiting factor precluding lymphocytes from genetically resistant mice from responding to HgCl2

Abstract: It is unclear how HgCl2 causes autoimmune disorders in genetically predisposed rodents. We investigated the cytokine profile induced by HgCl2 in vitro, and found a high frequency of IL-2-secreting cells in splenocytes from susceptible A.SW and BALB/c mice, whereas the frequency was low in cells from resistant DBA/2 mice. More IL-2-secreting cells were induced in splenocytes from the high responder A.SW mice than in cells from the intermediate responder BALB/c mice. Unexpectedly, a similar level of IL-4 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This suggests that low baseline levels of IL‐2, which are further reduced by exposure to Hg, play an important role in resistance to M‐HgIA in the A.TL strain. Indeed, Jiang and Möller [30] recently proposed that IL‐2 may be a limiting factor that prevents the lymphocytes in resistant DBA/2 mice from responding to Hg in vitro . Interestingly, it has been reported that self‐tolerance in mice is maintained by a CD25 + CD4 + subset of T‐cells that exert their suppressive effect by reducing expression of IL‐2 [31].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that low baseline levels of IL‐2, which are further reduced by exposure to Hg, play an important role in resistance to M‐HgIA in the A.TL strain. Indeed, Jiang and Möller [30] recently proposed that IL‐2 may be a limiting factor that prevents the lymphocytes in resistant DBA/2 mice from responding to Hg in vitro . Interestingly, it has been reported that self‐tolerance in mice is maintained by a CD25 + CD4 + subset of T‐cells that exert their suppressive effect by reducing expression of IL‐2 [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be evaluated if the inability of the Vβ7+ T cells to respond directly to HgCl 2 is due to an inadequate ligation of the CD28 molecule. It has been proposed that IL–2 is a limiting factor for mouse splenic lymphocytes to respond to HgCl 2 , since even spleen cells from non–responder mouse strains could respond in the presence of exogenous IL–2: ‘IL–2 may be a limiting factor precluding lymphocytes from genetically resistant mice from responding to HgCl 2 ’ [52]. On the other hand, it has also been shown that mouse splenocytes pretreated with HgCl 2 for 1–3 days and analysed the day after washing had a much higher in vitro reactivity to HgCl 2 compared to cells continuously exposed to HgCl 2 [53].…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, HgCl 2 modulates T cells by induction of interleukins (IL) (e.g., IL-1 b ) and immunoglobulins (Ig) (e.g., IgG and IgE) (Griem et al, 1998), and by altering expression of costimulatory molecules (Roos et al, 1996); Hg stimulation of B lymphocytes may also mediate autoimmunity (Druet et al, 1982;Rose, 1993). In rodents, other features of Hg-induced autoimmune disease include generation of autoreactive CD4 + T cells (inhibition of Th1 and enhancement of Th2 subsets); synthesis of autoantibodies; glomerulonephritis; hypergammaglobulinemia; and regulation by IL-2 (Lawrence & McCabe, 1995;Kosuda et al, 1994Kosuda et al, , 1998Jiang & Moller, 1999;Abedi-Valugerdi et al, 1999). Interestingly, significant induction of serum concentrations of IgA, IgG, and IgM (compared to nonexposed healthy subjects) was observed in human workers exposed to Hg occupationally .…”
Section: Hg-induced Immunotoxicity In Mammalian Speciesmentioning
confidence: 99%